Dinamika Kerapatan Vegetasi di Kawasan Hutan Dengan Tujuan Khusus Universitas Lambung Mangkurat Menggunakan Indeks EVI (2019–2024): Vegetation Density Dynamics in the Special Purpose Forest Area of Lambung Mangkurat University Using Enhanced Vegetation Index (2019–2024) - Rosadi, Hadi; Nur Shiba, Yasinta; Noor Hadi, Wirawan (JURNAL HUTAN TROPIKA, 2025)
The Special Purpose Forest Area (KHDTK) of Lambung Mangkurat University plays a vital role as a natural laboratory for research, education, and conservation. Monitoring vegetation cover is essential to evaluate the effectiveness of sustainable forest management. This study analyzes the temporal and spatial dynamics of vegetation cover in KHDTK ULM during 2019–2024 using the Enhanced Vegetation Index (EVI) derived from Google Earth Engine (GEE) and assesses the net change over the period. Sentinel-2 imagery was processed into annual composites in GEE and analyzed through EVI classification combined with spatial analysis in ArcGIS. The results show that mean EVI increased from 0.438 in 2019 to 0.529 in 2024, representing a 20.77% rise. Dense vegetation expanded by +1163.26 ha (+111.74%), while medium and non-vegetation classes declined significantly. These changes indicate a major transition from medium to dense vegetation, particularly in the forest core, where as reductions were concentrated along edges dominated by grasslands and open areas. The findings demonstrate that conservation, rehabilitation, and management efforts in KHDTK ULM have effectively enhanced forest recovery and provide a scientific basis for adaptive and sustainable forest education management.